Depth of Processing in Different Instructional Conditions and Iranian Learners’ Interpretation of English Inversion Structures - Shiva Kaivanpanah; Seyed Mohammad Alavi; Sara Rafsanjani Nejad (Journal of Modern Research in English Language Studies)
The idea of encouraging awareness in classrooms is not new, but research into awareness is beginning to encourage those involved in language teaching to think more systematically about how language presentation facilitate language awareness. Awareness can be promoted through focus on form activities as it triggers important cognitive processes in L2 acquisition. The effectiveness of various input- and output-based focus on form instructions on the acquisition of different grammatical structures and the role of awareness in each type is a matter for debate. The present study qualitatively investigated the effects of Processing instruction, Textual enhancement, and Text editing on L2 learners’ cognitive processes and the relationship between the learners’ level of awareness and their abilities to interpret English inversion structures. To do this, learners’ think-aloud verbalizations during instruction were recorded, transcribed, and coded. Criteria to decide which level of awareness they would fall into were slightly adapted from Leow, Hsieh, and Moreno (2008) to fit with the type of tasks employed in the study. Pretest-posttests design was also employed to measure learners’ interpretive abilities. The findings indicated that each instructional technique promoted different levels of awareness and depth of processing. The findings also provided explanations for the non-significant differences in performances between the Processing instruction and Text editing groups on an immediate posttest and outperformance of the Processing instruction group on a delayed posttest. Given the benefits that Processing instruction and Text editing brought about in the present study, both might be incorporated into a curriculum and serve as complementary tools for language teachers.